INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN TEACHING DIAGNOSTICS OF OPHTHALMOLOGICAL DISEASES (ON THE EXAMPLE OF GLAUCOMA AND DIABETIC RETINOPATHY) - Djoldasov Aybek (Bright Mind Publishing, 2025)
In the context of digital transformation of medical education, the introduction of innovative pedagogical technologies in the training of future ophthalmologists is of particular importance. The article discusses modern educational approaches - simulation training, augmented and virtual reality (AR/VR), online platforms and distance learning courses - in the context of their effectiveness in teaching the diagnosis of glaucoma and diabetic retinopathy. Data on improving the academic performance and clinical readiness of students using interactive methods are presented. Proposals are made to improve ophthalmological education in Uzbekistan and the CIS countries.
Keywords: Glaucoma, diabetic retinopathy, pedagogical technologies, AR/VR, simulation training, ophthalmology, distance learning.